2023
DOI: 10.1108/ijrdm-07-2022-0268
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the gamified customer experience in the retail environment

Abstract: PurposeRetailers increasingly are using gamification to make the customer experience (CX) more exciting and encourage favourable customer outcomes. This paper aims to conceptualise the gamified customer experience (GCX), including relevant affordances, and investigate its effects on key customer outcomes, as well as its influential factors.Design/methodology/approachThe authors conducted a qualitative interview study with retail customers and gamification experts, plus a scenario-based experiment to test the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(133 reference statements)
0
0
0
Order By: Relevance
“…The results indicated that gamification is associated with an improved CX, which supports the second hypothesis of this study. This finding is also consistent with the previous studies [25]. Using game elements in a non-game context can increase a desired behavior [68].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results indicated that gamification is associated with an improved CX, which supports the second hypothesis of this study. This finding is also consistent with the previous studies [25]. Using game elements in a non-game context can increase a desired behavior [68].…”
Section: Discussionsupporting
confidence: 93%
“…Customers are easily able to check their status and redeem the rewards as well [22].Recent research has examined how gamification can affect the real -world shopping experience, as seen in studies by Olsson et al [23] and Högberg et al [24]. A recent study [25] showed that game elements can lead to a more exciting customer experience (CX). This study used these finding to conceptualize "Gamified Customer Experience" that influences customer engagement, satisfaction and brand attitude.…”
mentioning
confidence: 99%